The Effect Of Additional Income On Employee Performance Through Work Discipline In Regional Secretariat Dairi Regency - Herbet Darwin Sianturi; Muhammad Isa Indrawan (Yayasan Multidimensi Kreatif, 2025)
Appropriate additional income and high work discipline are important factors in improving employee performance in government organizations. This study aims to find out and analyze the influence of additional income on employee performance mediated by work discipline in the Dairi Regency Regional Secretariat. This study uses a causal associative quantitative approach. The sample used was the entire employee population totaling 160 people, with a saturated sampling technique. Data analysis was carried out using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results of the study showed that additional income did not have a significant effect on employee performance, but had a positive and significant effect on work discipline, with a T-statistical value of 4.092 > 1.96 and a P-value of 0.000 < 0.05, which indicates that additional income encourages employees to be more disciplined in their work. Work discipline also had a positive and significant effect on employee performance, with a T-statistical value of 3.930 > 1.96 and a P-value of 0.000 < 0.05, which shows that improving work discipline can improve employee performance. In addition, work discipline was able to mediate the influence between additional income and employee performance, as shown by the T-statistical value of 3.884 > 1.96 and the P-value of 0.000 < 0.05. These results provide insight that additional income and work discipline are effective strategies in improving employee performance at the Dairi Regency Regional Secretariat.